2021
DOI: 10.1002/art.41615
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lesional Juvenile Myositis and Lupus Skin Reveals Overlapping Yet Unique Disease Pathophysiology

Abstract: Objective. Skin inflammation heralds systemic disease in juvenile myositis, yet we lack an understanding of pathogenic mechanisms driving skin inflammation in this disease. We undertook this study to define cutaneous gene expression signatures in juvenile myositis and identify key genes and pathways that differentiate skin disease in juvenile myositis from childhood-onset systemic lupus erythematosus (SLE).Methods. We used formalin-fixed paraffin-embedded skin biopsy samples from 15 patients with juvenile myos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 43 publications
(52 reference statements)
2
17
0
Order By: Relevance
“…Tubuloreticular inclusions can occur in OM, especially in lupus erythematosus, but were not present in our cases [ 65 , 66 ]. MxA upregulation was weak on scattered fibers, but was not in a perifascicular distribution in OM, consistent with the upregulation of type I IFN in childhood SLE [ 18 , 67 ].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Tubuloreticular inclusions can occur in OM, especially in lupus erythematosus, but were not present in our cases [ 65 , 66 ]. MxA upregulation was weak on scattered fibers, but was not in a perifascicular distribution in OM, consistent with the upregulation of type I IFN in childhood SLE [ 18 , 67 ].…”
Section: Discussionsupporting
confidence: 70%
“…Myositis, in conjunction with skin lesions, is also seen in other rheumatologic disorders, such as systemic lupus erythematosus (SLE), connective tissue diseases, and some monogenic autoinflammatory diseases, further impeding the diagnosis and treatment of jIIM [ 14 , 17 , 18 , 19 , 20 ]. Moreover, in jIIM patients with negative autoantibodies, finding a precise diagnosis can be problematic (although it is currently not known whether autoantibodies have the same relevance in children as in adults).…”
Section: Introductionmentioning
confidence: 99%
“…The finding of a stronger innate immune signature versus adaptive immune signature in juvenile DM compared to cSLE at both transcriptional and protein levels suggests differences in pathophysiology. Consistent with this, our previously published gene expression data identified a stronger type II IFN signature in cSLE skin lesions compared to juvenile DM skin lesions (11), supporting a larger role for adaptive immunity in cSLE. While innate immunity likely plays an important role in both juvenile DM and cSLE pathogenesis, the influence of innate immune mechanisms in regulation of cutaneous inflammation in juvenile DM as compared to cSLE has not been well studied to date.…”
Section: Discussionsupporting
confidence: 87%
“…50 Studies have also demonstrated that single nucleotide polymorphisms or altered copy number within mtDNA are associated with the development of adult idiopathic inflammatory myopathies. 51 These studies, taken together with the high mitochondrial content in skeletal muscle 52 and the growing interest in understanding immune cell function within inflamed tissues, 53 demonstrate that new research is needed to interrogate mitochondrial biology within biopsies from JDM muscle.…”
Section: Myositismentioning
confidence: 99%